2015
DOI: 10.1177/1740774515601679
|View full text |Cite
|
Sign up to set email alerts
|

Description of the types and content of phase 1 clinical trial consent conversations in practice

Abstract: Background/Aims All agree that informed consent is a process, but past research has focused content analyses post-consent or in one conversation in the consent series. Our aim was to identify and describe the content of different types of consent conversations. Methods We conducted a secondary analysis of 38 adult oncology phase 1 consent conversations, which were audio-recorded, transcribed, coded, and qualitatively analyzed for type and content. Results Four types of consent conversations were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…However, there are neither established communication guidelines for the information physicians should include during these discussions 14,17,50 nor patient-physician consensus on the most important information to discuss. [18][19][20][21][22][23][42][43][44][45][46] Therefore, it is vital to include current patients' voices and preferences in creating molecular testing guidelines. This study successfully identified patients' and physicians' preferences for molecular testing communication, patients' preferences for the method of receiving information, and physicians' preferences for communication aids.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there are neither established communication guidelines for the information physicians should include during these discussions 14,17,50 nor patient-physician consensus on the most important information to discuss. [18][19][20][21][22][23][42][43][44][45][46] Therefore, it is vital to include current patients' voices and preferences in creating molecular testing guidelines. This study successfully identified patients' and physicians' preferences for molecular testing communication, patients' preferences for the method of receiving information, and physicians' preferences for communication aids.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical observations, discrepancies have been identified between physician practice and patient preference for information. For example, although a majority of cancer patients report prognostic information as important and necessary, physicians frequently omit this information …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The American Society of Clinical Oncology (ASCO) has recognized the challenges of communicating effectively about such complex topics [13], and has called on clinicians to uncover and address communication problems that hinder ACP understanding [1]. Communication skills training programs that serve these aims are widely available to oncologists [46] and embedded in graduate medical education [7].…”
mentioning
confidence: 99%